SYNERGISTIC ACTION OF ZINGIBER OFFICINALE EXTRACT WITH ANTIBIOTICS (International Journal of Food and Nutritional Sciences, 2022)
The emergence of resistant strains of bacteria has seriously limited our ability to treat bacterialillness, and new antibiotics are desperately needed. In this study, the plant extracts were prepared byusing diff. solvents (Acetone, EtOH and MeOH). Antimicrobial activity of plant extracts,Antibiotics (Amoxicillin, Ceftazidime, Ciprofloxacin, Amphotericin-B and Fluconazole) andcombinations has been done by Agar well Diffusion method. The results of this study showed thatethanol and methanol extract show higher activity against selected pathogenic species. HPTLC hasbeen also performed to check if there any new compound formed or not by combination of extractand antibiotics. The findings of this study suggest that combining plant extract with antibiotics maybe effective in battling newly developed drug-resistant microbes